KEADILAN DI TEMPAT ASING: TEOLOGI GĒR DALAM KITAB ULANGAN DAN RELEVANSINYA BAGI KEHIDUPAN BERMASYARAKAT - Nugraha Vienshe (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2022)
This paper wants to show that the ethics toward strangers, shown in the Book of Deuteronomy, is relevant to use as a guide in living together and is an antithesis to the phenomenon of racism that still occurs today. Racism is a phenomenon of injustice against certain races or groups that are considered different, foreign, and weak. The phenomenon of racism can lead to more significant problems in life, such as conflicts and human tragedies. In contrast, the law in Deuteronomy expressly denies oppression of the